A novel finding in the work of Ricardo Palma: the manuscript of Anthology of Spanish poetry of 1893 - Pérez Garay, Carlos Alberto (2019)
This paper focuses on the history of a manuscript from the late nineteenth century written by Ricardo Palma, which was found in the NationalLibrary of Peru and holds valuable information to understand the life and work of one of the most representative Peruvians writers of all time.